2022
DOI: 10.1007/s00018-022-04167-8
|View full text |Cite
|
Sign up to set email alerts
|

FKBP51 modulates hippocampal size and function in post-translational regulation of Parkin

Abstract: FK506-binding protein 51 (encoded by Fkpb51) has been associated with stress-related mental illness. To identify its function, we studied the morphological consequences of Fkbp51 deletion. Arti cial Intelligence-assist morphological analysis identi ed that Fkbp51 knock-out (KO) mice possess more elongated CA and DG but shorter in height in coronal section when compared to WT. Primary cultured Fkbp51 KO hippocampal neurons were shown to exhibit larger dendritic outgrowth than wild-type (WT) controls, pharmacolo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 97 publications
6
13
0
Order By: Relevance
“…3A. The identi cation of a functional connection between Parkin and FKBP51 (Qiu et al, 2022), along with the established relationship between Pink1 and FKBP51 (Boonying et al, 2019), strengthens the argument that FKBP51 plays an important role in mitochondrial regulation. Our study further pointed out those DEG with higher FC between KO and WT and their involved functions.…”
Section: Resultssupporting
confidence: 53%
See 3 more Smart Citations
“…3A. The identi cation of a functional connection between Parkin and FKBP51 (Qiu et al, 2022), along with the established relationship between Pink1 and FKBP51 (Boonying et al, 2019), strengthens the argument that FKBP51 plays an important role in mitochondrial regulation. Our study further pointed out those DEG with higher FC between KO and WT and their involved functions.…”
Section: Resultssupporting
confidence: 53%
“…STRING analysis identi ed inter-connections between Fkbp51, Hsp90aa1 and Park2, and a hub of genes related to lipid and TAG biosynthesis and metabolism, brogenesis, immune response, cell cycle, and drug metabolism. We have previously demonstrated FKBP51 and Parkin binding using immuno uorescence (IF) and co-immunoprecipitation (Qiu et al, 2022). In the current study, we found that these two proteins co-localize in mitochondria.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…While, lowering the levels of FKBP5 reduced HTT in HD models both in vitro and in vivo [ 70 ]. FKBP5 knockout AD models exhibit few phenotypic changes or behavioral alterations [ 71 , 72 ] and, tau levels were reduced throughout the brains of Fkbp5 -/- mice [ 73 , 74 ]. These results supported the modulation of FKBP5 as a therapeutic target for neurological diseases.…”
Section: Discussionmentioning
confidence: 99%